The Gazeta de Lisboa and the earthquake of 1755: reading between the lines - Belo, André (2000)
What was a newspaper in the Old Regime? Departing from the Gazeta de Lisboa's brief and informative treatment of the Lisbon earthquake of 1755, this article attempts to reconstruct the categories that characterised newspaper writing at the time. This was more like history than information about current affairs directed at the public at large.